Strategi Pengembangan UMKM Berbasis Potensi Lokal Melalui Penerapan Digitalisasi Kewirausahaan - Nur Fahmi Ahmad; Muthi Syahidah; Andi Ummul Khair; Mustamin Mustamin; Widi Astutik; Achmad Zulkarnaen (Lamahu: Jurnal Pengabdian Masyarakat Terintegrasi, 2026)
The low use of digital technology by Micro, Small, and Medium Enterprises (MSMEs) based on local potential is still an obstacle in increasing competitiveness and business sustainability in the midst of digital economy transformation. This condition is also experienced by MSMEs in Cimpiga Village, Camba District, Maros Regency, most of which are still managed conventionally with limited market reach. This Community Service activity aims to increase digital literacy and entrepreneurial capacity of MSMEs through the implementation of entrepreneurial digitalization. A participatory approach is used to encourage active involvement of partners in the learning process and application of digital technology. The results of the activity showed an increase in the understanding, digital skills, and marketing capabilities of MSMEs, followed by a change in business patterns towards a more adaptive use of digital media. These findings show that entrepreneurship digitalization is effective as a strategy for empowering MSMEs based on local potential and contributes to increasing competitiveness and readiness of business actors in facing the dynamics of the digital economy in a sustainable manner.